29.4k views
2 votes
If f(x) = -3x + 4, find f(3x + 3)

2 Answers

0 votes

Hey there!!

f ( x ) = -3x + 4

Find f ( 3x + 3 )

In order to solve this, we will need to substitute 3x + 3 instead of x

...f ( 3x + 3 ) = - 3 ( 3x + 3 ) + 4

...f ( 3x + 3 ) = -9x - 9 + 4

...f ( 3x + 3 ) = -9x - 5

Hence, the answer is -9x - 5

Hope my answer helps!!


User Vin
by
5.1k points
3 votes

Remark

What this is telling you to do is put 3x + 3 in the question wherever there was an x to start with.

Solution

f(x) = -3x + 4

f(3x + 3) = - 3(3x + 3) + 4

f(3x + 3) = -3*3x + (-3)*(3) + 4

f(3x + 3) = - 9x - 9 + 4

f(3x + 3) = -9x - 5 <<<<< Answer

User Dpbklyn
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.